Truth and kisses - Friedman, Laurie B., 1964- (Friedman, Laurie B., 1964- Mostly miserable life of April Sinclair, 2014)
Diary entries reveal thirteen-year-old April Sinclair's complicated best-friend/love triangle, her new friendship, a busy dance team schedule, and a closer relationship with Matt Parker that surprises her and everyone else.